Efficacy of Intra-Articular Polynucleotides Associated With Hyaluronic Acid Versus Hyaluronic Acid Alone in the Treatment of Knee Osteoarthritis: A Randomized, Double-Blind, Controlled Clinical Trial. Issue 1 (January 2020) - Dallari, Dante; Sabbioni, Giacomo; Del Piccolo, Nicolandrea; Carubbi, Chiara; Veronesi, Francesca; Torricelli, Paola; Fini, Milena
Abstract : Objective: Pain and range of motion loss are the main clinical features of osteoarthritis (OA). Hyaluronic acid (HA) is one of the infiltrative therapies for OA treatment; however, its effectiveness is a matter of an ongoing debate in clinical practice . Polynucleotides (PNs), a DNA-derived macromolecule with natural origin and trophic activity, were found to favor cell growth and collagen production, in preclinical and clinical studies regarding cartilage regeneration. This study aimed at evaluating whether injection of PNs, in combination with HA [PNs associated with HA (PNHA)], can ameliorate pain and function of knees affected by OA, more than HA alone. Design: A randomized, double-blind, controlled clinical trial. Patients: The study enrolled 100 patients, then randomized to receive PNHA or HA alone (3 weekly knee I.A. injections). Interventions and Main Outcome Measures: Pain reduction, decrease of proinflammatory synovial fluid (SF) factors, and improvement in knee function were evaluated by Knee Society Score and WOMAC scores, after 2, 6, and 12 months and by biochemical and immunoenzymatic analyses of SF at the end of the treatment. Results: Knee Society Score total score and pain item significantly ameliorated in both groups, showing better results in PNHA- than in the HA-treated group. A significant reduction in the WOMAC score was observed over time for both groups. No significant adverse events were reported in either group. Conclusions: These findings suggest that I.A. injection of PNs, in combination with HA, is more effective in improving knee function and pain, in a joint affected by OA, compared with HA alone.